PERANAN PENDIDIKAN ISLAM DALAM MENINGKATKAN MORAL BANGSA - Badriyah, Siti (LPPI Universitas Al-Qolam Malang, 2014)
Humanistic education is expected to improve human spirituality by sending the humankind back to their nature as the superior creature. ‘Humanistic human’ produced by humanistic education is supposed to be able to think, feel, sense and act based on the humane noble values, instead of individualism and egoism.The youth have courage, open-mind as well as abundant of vitality and dynamics. That’s why they’re called the hope of the nation. The development of morality and creativity of the youth can be conducted simultaneously with the development of Islamic education in family, school, and community in order to create supportive, educative atmosphere. This, in turn, reflects the ideal, integral, and culturally rooted Islamic education. This can also liberate the youth from the shackle of infidelity, poverty, violence, as well as immorality.It’s the duty of the youth to have intelligent capability, braveness, honesty and loyalty towards the values of the truth. The youth are the future leaders, they hold the destiny of the nation.Keywords: Islamic education, humanist, youth